Iron deposition in Parkinsonisms: A Quantitative Susceptibility Mapping study in the deep grey matter. Issue 133 (December 2020) - Fedeli, Maria Paola; Contarino, Valeria Elisa; Siggillino, Silvia; Samoylova, Nina; Calloni, Sonia; Melazzini, Luca; Conte, Giorgio; Sacilotto, Giorgio; Pezzoli, Gianni; Triulzi, Fabio Maria; Scola, Elisa
Highlights: In-vivo automatic quantitative analysis of magnetic susceptibility in the brain. Susceptibility differences among primary atypical parkinsonisms and Parkinson's disease. Susceptibility changes in red nuclei might help in Progressive Supranuclear Palsy diagnosis. Susceptibility changes in thalami are detected in Cortico-Basal Degeneration. Abstract: Purpose: The aim of the study is to quantify the susceptibility in deep grey nuclei that are affected by pathological processes related to iron accumulation in patients with Parkinson's disease and primary atypical parkinsonisms such as Progressive Supranuclear Palsy, Multiple System Atrophy and Cortico-Basal Degeneration, in order to assist the differential diagnosis among parkinsonian syndromes. Methods: We enrolled 49 patients with Parkinson's disease and 26 patients with primary atypical parkinsonisms. Automatic segmentation of putamen, globus pallidus, caudate nucleus and thalamus and manual segmentation of red nuclei and substantia nigra were performed, and region of interest-based Quantitative Susceptibility Mapping analysis were performed. Statistical comparisons of the mean susceptibility values in the segmented brain regions were performed among primary atypical parkinsonisms and Parkinson's disease. Results: Susceptibility values in red nuclei were increased in Progressive Supranuclear Palsy patients compared to parkinsonian phenotype Multiple System Atrophy (p = 0.004), and Parkinson's disease patients (p = 0.006). Susceptibility in thalamus was decreased in Cortico-Basal Degeneration patients compared to Parkinson's disease (p = 0.006), Multiple System Atrophy with cerebellar phenotype (p = 0.031) and parkinsonian phenotype (p = 0.001) patients, and in Progressive Supranuclear Palsy patients compared to Multiple System Atrophy with parkinsonian phenotype patients (p = 0.012). Conclusions: Quantitative Susceptibility Mapping allows the depiction and quantification of different patterns of iron deposition in the deep gray nuclei occurring in primary atypical parkinsonisms and Parkinson's disease and it may help as a non-invasive tool in the differential diagnosis between parkinsonian syndromes.